2017
DOI: 10.3904/kjim.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS and abnormal creatine kinase-MB are predictors of coronary artery disease in patients with angina and normal electrocardiographys

Abstract: Background/AimsPatients with symptoms of coronary artery disease (CAD) often display normal tracings or only nonspecific changes on electrocardiography (ECG). The aim of this study was to explore strategic elements of the ECG and other potential factors that are predictive of CAD in this scenario.MethodsThis was an observational study of 142 patients with the chief complaint of chest pain, each of whom presented with a normal ECG and was subjected to emergency coronary angiography (CAG). Two population subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In addition, a previous study demonstrated that an elevated serum CK-MB in cancer patients may be associated with cardiac insufficiency, severe illness status, and have high mortality ( 20 ). Even a slight increase in CK-MB indicated the possibility of myocardial infarction ( 21 ). There has been no retrospective report focusing on CK, CK-MB and anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study demonstrated that an elevated serum CK-MB in cancer patients may be associated with cardiac insufficiency, severe illness status, and have high mortality ( 20 ). Even a slight increase in CK-MB indicated the possibility of myocardial infarction ( 21 ). There has been no retrospective report focusing on CK, CK-MB and anti-angiogenic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although elevated levels of CK-MB are well known to be associated with coronary artery disease (9), there was no significant difference in the level of CK-MB regardless of the presence of chest pain or abdominal pain in this study. While the exact mechanism about elevation of troponin-I is not fully understood in PSVT, the increased myocardial oxygen demand and decreased myocardial oxygen delivery due to shortened diastolic filling during paroxysmal attack are considered to be the result of a transient myocardial ischemia (4,5,10). Similarly, this study found that patients with chest pain had 4 Iran J Pediatr.…”
Section: Discussionmentioning
confidence: 73%
“…Elevation of these serum markers in this study did not exceed the normal upper limit, but it may indicate a tendency for long-term use to accumulate toxicity. In addition, a previous study demonstrated that a slight increase in CK-MB may be associated with several small areas of myocardial necrosis 18 , and even a slight increase in CK-MB indicated the possibility of coronary heart disease or myocardial infarction 23 , 24 .…”
Section: Discussionmentioning
confidence: 97%